2008
DOI: 10.1118/1.2836416
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of neural network approaches for on‐line prediction in IGRT

Abstract: Image-guided radiation therapy aims to improve the accuracy of treatment delivery by tracking tumor position and compensating for observed movement. Due to system latency it is sometimes necessary to predict tumor trajectory evolution in order to facilitate changes in beam delivery. Neural networks (NNs) have previously been investigated for predicting future tumor position because of their ability to model non-linear systems. However, no attempt has been made to optimize the NN training algorithms, and no men… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 35 publications
1
38
1
Order By: Relevance
“…This value is in between the range of latencies (50 to 1400 ms) observed in some image‐guided adaptive radiotherapy systems . It is well‐known that prediction accuracy deteriorates as the prediction horizon increases …”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…This value is in between the range of latencies (50 to 1400 ms) observed in some image‐guided adaptive radiotherapy systems . It is well‐known that prediction accuracy deteriorates as the prediction horizon increases …”
Section: Discussionmentioning
confidence: 71%
“…Various prediction models have been investigated for use during tracking of tumor motion in radiotherapy . These include: linear prediction, auto‐regressive moving average, stationary linear regression, sinusoidal modeling, adaptive filters, Kalman filters, and neural networks . In three of the comparative studies, a neural network has been shown to outperform the other prediction models .…”
Section: Introductionmentioning
confidence: 99%
“…The CCA is optimal way to respect correlations and at the same time to find a corresponding correlation, in which the correlation matrix between the variables is diagonal and the correlations on the diagonal are maximized. In fact, the dimensionality of these new bases is equal to or less than the smallest dimensionality of the two variables (35) . By applying CCA algorithm, a small amount of data will be lost when more than 90% of canonical correlation of all markers is covered.…”
Section: Methodsmentioning
confidence: 99%
“…Boosting methods have drawn lots of attention since it was proposed in 1990 [20,21,22], and keeps active in wide range of research fields and applications considering its excellent performance [23]. There is a popular believe that the ability of anti-overfitting is the key to interpreting its great performance and broad adaptability [24]. Gradient boosting estimates iteratively.…”
Section: Gradient Boosting Machinementioning
confidence: 99%